Shifting Economic Values in Generation Z Marriages: A Study of Qana'ah and Anti-Prestige in Simple Marriages at the KUA - Misi Anggraini; Ahmad Wira; Aidil Novia (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2026)
This study examines the shift in economic values underlying the phenomenon of Generation Z’s simple marriage at the KUA (without lavish receptions) from the perspective of Islamic economic ethics. Rooted in the concepts of qana’ah (contentment with simplicity) and anti‑showiness, the research highlights how this generation prioritizes long‑term well‑being and financial responsibility over social display. Using a qualitative approach, the study employs in‑depth interviews, discourse analysis of social media content, and case studies of couples who chose minimal‑ceremony marriages, supported by normative analysis of fiqh and economics literature. The results show that the preference for simple weddings reflects a growing ethical consciousness, where qana’ah and rejection of tabarruj and consumerist gifting function as moral boundaries. The findings indicate that this trend is not merely economic rationality but a value‑based transformation in marital culture. The discussion emphasizes that the KUA becomes a symbol of legal and ethical simplicity, aligning with Islamic economic principles of moderation, justice, and avoidance of extravagance.